Description of a new species of the melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil - Ywamoto, Eric Venturini [UNESP]; Nielsen, Dalton Tavares Bressane; Oliveira, Claudio [UNESP] (Magnolia Press, 2020)
A new species of the genus Melanorivulus belonging to the Melanorivulus pictus species group is herein described, from a tributary of the Rio Grande, Rio Paraná basin, São Paulo State, Brazil. The new species can be distinguished from all other species of the Melanorivulus pictus species group by the unique presence of sides of body of males light bluish gray with 10-12 oblique red bars, 8 of which chevron-like, bifurcated and complete, i.e., running from dorsum to ventral area, and 2-4 incomplete, with vertices of the chevron-like bars along midbody, pointing forward. Comments on the putative relationships of the new species, as well as concerning its conservation status, are presented.
Keywords: Cerrado; Killifishes; Melanorivulus apiamici; Melanorivulus leali; Rio Grande basin; Rivulus